Antioxidant status of the organisms of young bulls in the conditions of lead-cadmium load and effect of correcting factors - SlobodianS. О.; Gutyj, B. V.; Darmohray, L. M.; Povoznikov, M. G. (Regulatory Mechanisms in Biosystems, 2021)
Prolonged ingress of heavy metals into the organisms of animals, even in low concentrations, causes a number of toxic impacts, affecting various organs and systems. The objective of this study was to research parameters of enzymatic and non-enzymatic links of the system of antioxidant protection of the organism of young cattle in the condition of lead-cadmium load and the effect of Metisevit Plus feed additive. Studies were conducted on the basis of the Private Agricultural Company “Ukraina”, located in Dubrovytsia district of Rivne Oblast, using 12 six-month old bulls of Ukrainian Black Pied Dairy breed divided into two groups, each consisting of 6 animals. Bulls of the control group received the standard diet. The bulls of the experimental group were fed with Metisevit Plus feed additive in the dose of 0.5 g/kg of feed. The contents of lead and cadmium in feed at the enterprise were determined to be high. According to the conducted studies, it was determined that in conditions of cadmium and lead load, there is a decrease in activity of glutathione link of the system of antioxidant protection of the organism of bulls. Feeding the bulls of the experimental group with Metisevit Plus feed additive for 30 days led to increase in the levels of non-enzymatic and enzymatic activities of the glutathione system. Significant increase in the level of reduced glutathione was recorded on days 30 and 40 of the experiment. Consumption of Metisevit Plus by the animals of the experimental group promoted increase in the activity of catalase and superoxide dismutase starting on the 20th day of the experiment. On days 30 and 40 of the experiment, the activity of the studied enzymes ranged within the physiological values. Therefore, the studies conducted on the bulls indicate that in the conditions of cadmium and lead load the feed additive Metisevit Plus fed to the bulls activated the system of antioxidant protection by increasing the levels of enzymatic and non-enzymatic links. When feeding bulls of the experimental group with Metisevit Plus feed additive, we determined significant decreases in diene conjugates and TBA-active products in their blood starting already on the 10th day of the experiment. On days 20 and 30 of the experiment, the level of diene conjugates in the blood of animals of the experimental group decreased by 14.5% and 24.0%. Efficiency of the feed additive may be explained by the effect of its constituents on the main pathogenic links of the pathological process caused by cadmium and lead. As indicated in the studies, liquidation of the syndrome of endogenous intoxication restores the functional condition of cellular membranes of the liver, protein-synthesizing function of the liver, increases the antioxidant status of the organisms of bulls. The studies we conducted confirm the expedience of using feed additive Metisevit Plus to prevent lead-cadmium toxicosis.